2002
DOI: 10.1128/jb.184.8.2088-2099.2002
|View full text |Cite
|
Sign up to set email alerts
|

Xis Protein Binding to the Left Arm Stimulates Excision of Conjugative Transposon Tn916

Abstract: Xis protein enhances excision in a manner similar to the excisionase protein of bacteriophage , serving an architectural role in the stabilization of protein-nucleic acid structures required for strand synapsis. However, our finding that excision in E. coli is significantly enhanced by the host factor HU, but does not depend on the integration host factor or the factor for inversion stimulation, defines clear mechanistic differences between Tn916 and bacteriophage recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 66 publications
3
18
0
Order By: Relevance
“…Thus, the himA mutation appears to have a modest effect on V. cholerae growth. These results are similar to what has been reported for fis and himA in E. coli (8,14,22).…”
Section: Resultssupporting
confidence: 82%
“…Thus, the himA mutation appears to have a modest effect on V. cholerae growth. These results are similar to what has been reported for fis and himA in E. coli (8,14,22).…”
Section: Resultssupporting
confidence: 82%
“…For example, the small Xis protein encoded by mycobacteriophage L5 is predicted to bind to four related sequence motifs spaced Ϸ10 bp apart to form a stable and bent DNA complex (27). The low molecular weight Xis protein from the Tn916 transposon also exhibits similar binding behavior and produces large footprints that contain hypersensitive cleavage sites characteristic of wrapped or bent DNA (31,32). It seems likely that many of these proteins also assemble into nucleoprotein filaments, which function to stabilize recombinogenic higher-order structures.…”
Section: The Structure Of Three Xis Proteins Bound To the X1-x2 Dna Smentioning
confidence: 99%
“…2). DnaseI protection assays with Xis show that it binds to a region which exceeds what was expected based on the size of the protein [1,5]. This can be explained by postulating that DNA is wrapped around Xis, thus protecting a larger region.…”
Section: Functional Analysis Of Int and Xismentioning
confidence: 79%
“…Another possibility is that Xis may bind to the DNA in the crook of a 2018 P. Mullany, A. P. Roberts and H. Wang Integration and excision static bend. Therefore, Xis may facilitate the binding of Int to DNA by bending the target DNA (but see below for further discussion of this point) or by formation of proteinprotein or protein-DNA complexes, or both [1,5]. Recent work has shown that mutations at the right end of Tn916 that decrease the binding of Xis result in a higher frequency of excision compared with the wild type, indicating that Xis inhibits excision [1].…”
Section: Functional Analysis Of Int and Xismentioning
confidence: 95%
See 1 more Smart Citation